Transitional care interventions to reduce emergency department visits in older adults: A systematic review - Latifah Jehloh; Praneed Songwathana; Wipa Sae-Sia (Belitung Nursing Journal, 2022)
Background: Preventable illnesses cause many emergency department visits in older adults, which can be minimized by implementing appropriate transitional care interventions. However, the most effective transitional care strategies for older adults are unknown. Objective: To discover and consolidate transitional care interventions that can help older people avoid going to the emergency department. Methods: From January 2011 to August 2021, PubMed, The Cochrane Library, CINAHL, Web of Science, ProQuest, and The JAMA Network were used to search. Two authors independently screened and selected papers, assessed the risk of bias, and extracted data into a standardized form in accordance with Cochrane guidelines. For the risk of bias in studies, the RevMan 5.4.1 program was utilized. Results: Six randomized controlled trials, four non-randomized controlled trials, and three retrospective investigations were among the 13 studies examined. All studies evaluated emergency department visits but in different periods (ranging from 1-12 months after discharge) and with varying groups of baselines (pre-post intervention and between groups). The multi-component strategies, either pre or post-discharge phase using high-intensity care delivered within six months of discharge, were implemented in transitional care that had been shown to reduce emergency department visits in older adults. Conclusion: To prevent emergency department visits by older patients, nurses should arrange for a high-intensity transitional care intervention that involves both pre-and post-discharge interventions. The effectiveness of the intervention in reducing emergency department visits in older adults is difficult to determine due to inter-study heterogeneity and poor methodological quality. There is a need for more evidence-based research with consistent and trustworthy effect assessments. PROSPERO registration number: CRD42021261326